Development of an untraditional technique to control the structure of the output flow from a vortex chamber - Turyk, Volodymyr; Kochin, Viktor; Moroz, Volodymyr; Miliukov, Dmytro (Eastern-European Journal of Enterprise Technologies, 2022)
A technique of using coherent vortex formations of the dead-end zone of the vortex chamber of the end type as a controlling factor influencing the structure and characteristics of the output flow has been developed. The kinematic parameters of the flow relative to chambers with elongated and extremely short dead-end parts in the range of Reynolds numbers according to the parameters of the nozzle Re=47080–86530 were investigated. The reaction of the flow structure in the output sections of the vortex chambers was determined experimentally using thermoanemometry. Profiles of time-averaged transversal and axial velocity projections, as well as corresponding values of the relative intensity of velocity pulsations, were obtained. It was found that at Re=86530, the elongation of the dead-end part of the chamber leads to a decrease in the initial cross-section of the transversal component by 15 % with an increase in the axial component by 19.7 %, and, at Re=47080, to a decrease in the transversal component by 21 % with an increase in the axial component by 8.5 %. This indicates the redistribution of kinetic energy from transversal to axial energy motion, which is confirmed by the analysis of the corresponding intensity profiles of the velocity pulsations in the output section of the chamber in the near-wall and near-axis zones of the flow. The integral intensity of the velocity pulsations along the initial cross-section of comparable chamber designs increases in a chamber with an elongated dead-end part with almost no additional energy losses. The obtained results form the basis of a rational method of controlling the macro- and microstructure of flows, which determines the efficiency of mass exchange and heat exchange processes in vortex chambers of the end type. Such designs are characteristic of vortex mixers, burners of industrial furnaces, furnace devices of hot water and steam boilers, and other technological and power equipment